Opportunity Recognition Amongst Different Types Of Entrepreneurs - Atwal, Jaskaran (2006)
Opportunity recognition and entrepreneurship have yet to be emancipated from theoretical vagueness and achieve transparency. As a result the communities with a valid interest in these areas of theory have been deprived of clarity.